Remediation of Heavy Metal Contaminated Soils - Alpaslan, Bilge (My University, 1999)
Most of the available remediation technologies for the treatment of heavy metal contaminated soils are very expensive and result in residues requiring further treatment. However, stabilization/ solidification (immobilization) techniques, which are designed to decrease leaching potential of heavy metals from soil, provide very cost effective solution for heavy metal contaminated soils. Thus, nowadays there is an increasing application of immobilization techniques for the heavy metal contaminated sites. In this study, it was focused on the development of most efficient immobilization technology especially for Pb metal and also Cu and Fe metals. For this purpose, batch, TCLP and column experiments were conducted both for soil samples spiked with Pb and soil sample from an old smelting facility at Northern Cyprus. From TCLP experiments, it was found that lime and cement are the most efficient immobilization additives for Pb metal at 1:15 additive:soil mixing ratio. The same experiments also showed that for both Cu and Fe metals, lime and cement have their highest immobilization efficiencies of 94% at 1:15 ratio and 90% at 1:20 ratio respectively . Moreover, column experiments results showed that at 1:15 lime:soil mixing ratio, less than 1% of Fe and approximately 10% of Cu initially presented in the soils were leached .

Ağır metallerle kirlenmiş toprakların iyileştirilmesi için mevcut teknolojilerin çoğu oldukça pahalı teknolojiler olup iyileştirme sonunda arıtım gerektiren artıklar bırakmaktadır. Ancak, ağır metallerin topraktan sızmasını azaltmak için geliştirilen stabilizasyon/ solidifikasyon (immobolizasyon) teknikleri bu topraklar için oldukça ekonomik çözüm sağlamaktadır. Bu nedenle günümüzde ağır metallerle kirlenmiş toprakların immobolizasyon teknikleri kullanılarak iyileştirilmesinde bir artış vardır. Bu çalışma, başta Pb metali olmak üzere Cu ve Fe metalleri üzerinde en yüksek verime sahip immobilizasyon tekniğinin geliştirilmesi amacıyla gerçekleştirilmiştir. Bu amaç doğrultusunda, Pb ile kirletilmiş toprak numunelerinde ve Kuzey Kıbrıs'ta bulunan eski bir maden işleme sahasından alınan toprak numunesinde kesikli reaktör, TCLP ve kolon deneyleri gerçekleştirilmiştir. TCLP deney sonuçları, kireç ve çimentonun 1:15 bağlayıcı:toprak karışım oranında Pb metali üzerinde en yüksek verime sahip inorganik bağlayıcılar olduğunu göstermiştir. Aynı deney sonuları kirecin Cu ve Fe metalleri üzerinde sırasıyla 1:5 oranında % 94 ve 1:20 oranında % 90 immobilizasyon verimine sahip olduğunu ortaya koymuştur. Bu sonuçlara ilave olarak, kolon deneyi sonuçları 1:15 kireç:toprak karışım oranında başlangıç Fe ve Cu değerlerinin sırasıyla %1'den azının ve yaklaşık %10'nun sızdığını göstermiştir.
Keywords: Kimya mühendisliği ve ilgili konular; METALLER; Metalürji